Challenges towards export performance among Small and Medium Enterprise (SME) in Malaysia / Nurhajar Mohammad Yunus - Mohammad Yunus, Nurhajar (Faculty of Business and Management, 2017)
This research aims to investigate the challenges towards export performance among SME in Malaysia. Exporting can be described as a function of international trade whereby goods produced in one country are shipped to another country for future sales or trade. (businessdictionary, 2017)1. The research looked at three challenges cited as financial, procedural and international experience. The study was guided by the research objectives: to identify relationship between financial and export performance among SME in Malaysia, to identify relationship between procedural and export performance among SME in Malaysia and to identify relationship between international experience and export performance among SME in Malaysia. The research adopted causal research to collect quantitative by use of primary data questionnaires, this was preferred as it could enable the researcher to obtain complete and possible accurate information. The population was 70 firms , and the sample size was 59 and the response rate was 85%. The data collected was then analysed by using SPSS. The presentation of data was by tables with frequencies, mean and percentage to show the statement rate under study. Pearson correlation coefficient is used to measure independent variables and the dependent variable through its strength of relationship. The data collected for this research paper through questionnaires that are distributed to the owner and managers of SME in Malaysia that registered with Federal Agricultural Marketing Authority (FAMA)